Differential Molecular Responses of Rapeseed Cotyledons to Light and Dark Reveal Metabolic Adaptations toward Autotrophy Establishment - He, Dongli; Damaris, Rebecca N.; Fu, Jinlei; Tu, Jinxing; Fu, Tingdong; Xi, Chen; Yi, Bin; Yang, Pingfang (Frontiers in Plant Science, 2016)
Photosynthesis competent autotrophy should be established during the postgerminative stage of plant growth. Among the multiple factors, light plays a decisive role in the switch from heterotrophic to autotrophic growth. Under dark condition, the rapeseed hypocotyl extends quickly with an apical hook, and the cotyledon is yellow and folded, and maintains high level of the isocitrate lyase (ICL). By contrast, in the light, the hypocotyl extends slowly, the cotyledon unfolds and turns green, the ICL content changes in parallel with the cotyledon greening. To reveal metabolic adaptations during the establishment of postgerminative autotrophy in rapeseed, we conducted comparative proteomic and metabolomic analyses of the cotyledons of seedlings grown under light versus dark conditions. Under both conditions, the increase of the protease, fatty acids β-oxidation and glyoxylate-cycle related proteins was accompanied with rapid degradation of the stored proteins and lipids with an accumulation of the amino acids, while light condition partially retarded these conversions. Light significantly induced the expression of chlorophyll-binding and photorespiration related proteins, resulting in an increase of the reducing-sugar. However, the levels of some chlide conversion, Calvin-cycle and photorespiration related proteins also accumulated in dark grown cotyledons, implying that the transition from heterotrophy to autotrophy is programmed in the seed rather than induced by light. Various anti-stress systems, e.g., redox related proteins, salicylic acid, proline and chaperones, were employed to release the oxidative stress, which was mainly derived from lipid oxidation or photorespiration, under both conditions. This study provides a comprehensive understanding of the differential molecular responses of rapeseed cotyledons to light and dark conditions, which will facilitate further study on the complex mechanism underlying the transition from heterotrophy to autotrophy.